Sistem Informasi Pelayanan Orang Tua Menggunakan Rule-Based Decision Support System untuk Meningkatkan Transparansi dan Komunikasi Antara Sekolah dengan Orang Tua di SMK Bandung Percut Sei Tuan - Fakhrizal, Fiqri; Kurniawan R, Rakhmat (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research develops a decision support system using the Rule-Based Decision Support System (RB-DSS) method to enhance transparency and communication between the school and parents of students at SMK Bandung 1 Percut Sei Tuan, Deli Serdang. The research methodology involves data collection through literature reviews, interviews, and direct field observations. The collected data is analyzed and processed using the RB-DSS algorithm. The criteria included in the decision support system encompass academic grades, attendance, school fee payments, and environmental development. The study demonstrates that the RB-DSS decision support system can deliver more precise and effective results, significantly improving transparency and communication between the school and parents within the school environment. This enhanced communication fosters a collaborative atmosphere, ensuring that parents are well-informed and actively engaged in their children's educational progress